Technical vocabulary size among engineering undergraduates according to field of study at Universiti Malaysia Pahang - Amri Muaz, Azmimurad; Najah, Osman (Novelty Journals, 2018)
English for Specific Purposes (ESP) was designed to appeal learners learning languages in specific disciplines. ESP concerns on lexical words that are designed explicitly or have their own definition in specific fields. As engineering students work with texts such as manuals and procedures that contain an abundance of technical terms that have specific meaning in the engineering field, the vocabulary knowledge of technical terms is crucial for them to understand the texts. Nevertheless, engineering students were found to have difficulties whenever they encountered texts filled with technical terms. Hence, this study aims to investigate the vocabulary size of technical vocabulary among engineering students at Universiti Malaysia Pahang. This research employs mixed method design as both quantitative and qualitative paradigms are involved in this research. The instruments used in this research are technical vocabulary test and semi-structured interview. The test was used in collecting quantitative data while the semi-structured interview was used in collecting qualitative data. The test was administered to 150 students majoring in five different engineering courses who were currently on their third and fourth year of study whereas the interview involved 12 students from five respective engineering courses. The findings show that there is a significant difference in technical vocabulary size among engineering undergraduates based on their field of study.